Breaking the conflict trap : civil war and development policy - Collier, Paul; Hegre, Håvard; Elliott, V. L.; Hoeffler, Anke; Reynal-Ouerol, Marta; Sambanis, Nicholas (World Bank policy research report., 2003)
"Breaking the Conflict Trap identifies the dire consequences that civil war has on the development process and offers three main findings. First, that civil war has adverse ripple effects, which are often not taken into account by those who determine whether wars start or end. Second, some countries are more likely than others to experience civil war conflict and therefore the risks of civil war differ considerably according to a country's characteristics, including its economic stability. Finally, Breaking the Conflict Trap explores viable international measures that can be taken to reduce the global incidence of civil war and proposes a practical agenda for action." "This book should serve as a wake-up call to anyone in the international community who still thinks that development and conflict are distinct issues. This book will also be of interest to researchers, academics, and anyone interested in conflict and post-conflict resolution."--BOOK JACKET.